Women entrepreneurs:‘we cannot have change unless we have men in the room’ - Irene Kamberidou (Journal of Innovation and Entrepreneurship, 2013)
What is being done to support female entrepreneurship and in particular promote the ways in which information and communication technologies (ICTs) can encourage and facilitate it? Is today's business climate more inviting to women entrepreneurs? Are women equipped to thrive in this digital age? Current, future, and aspiring women entrepreneurs responded to these questions, and many more, at the recent European conference in Athens, Greece ‘More Technologies? More Women entrepreneurs!’ at which Madi Sharma, member of the European Economic and Social Committee argued that ‘we cannot have change unless we have men in the room.’ The European conference showed women - and men - the advantages and opportunities that ICTs can offer them for the development of their business initiatives. It also presented 12 European projects that focus on women's entrepreneurship and how ICT facilitates and fosters it. The European Commission is dynamically promoting, supporting, and encouraging female entrepreneurship. Europe needs more women entrepreneurs and actions are being taken to overcome the obstacles and change mindsets. This paper examines discussions and research on female entrepreneurial activity and provides Tips from successful women entrepreneurs who tell how they have been using new technologies - and social media in particular - to excel in their careers and balance their professional and family lives. Accordingly, this paper begins with an examination of the current research findings on social women’s new models of work, levels of engagement, and transformational leadership styles. Women share content in multiple ways, and working online has been a financial windfall for many, including stay-at-home moms and homemakers. More women are doing what comes ‘naturally’, taking advantage of their so-called natural strengths, such as ‘listening’, sharing, building relationships, and creating a culture of collaboration. Keywords: Gender, Technology, Women entrepreneurs, ‘Feminine’ skills, Leadership qualities, Social media ------------------------------------------------------------------------------------------------ <dl id="citeas" class="citation-info u-highlight-target u-mb-16"> Cite this article as: Kamberidou, I. J Innov Entrep (2013) 2: 6. https://doi.org/10.1186/2192-5372-2-6 </dl> DOI https://doi.org/10.1186/2192-5372-2-6 Publisher Name Springer Berlin Heidelberg Online ISSN 2192-5372 About this journal <a id="reprintsandpermissions-link" class="u-external" href="https://s100.copyright.com/AppDispatchServlet?publisherName=Springer&orderBeanReset=true&orderSource=SpringerLink&author=Irene+Kamberidou&authorEmail=irene.kamberidou%40womenandtechnology.eu&issueNum=1&contentID=10.1186%2F2192-5372-2-6&openAccess=true&publicationDate=2013&startPage=6&volumeNum=2&title=Women+entrepreneurs%3A+%E2%80%98we+cannot+have+change+unless+we+have+men+in+the+room%E2%80%99&imprint=Kamberidou%3B+licensee+Springer.&publication=2192-5372&authorAddress=Gr%C3%B8nland+58%2C+Drammen%2C+N-3045%2C+Norway" target="_blank" title="Visit RightsLink for information about reusing this article">Reprints and Permissions